Hydrogen from renewables: Supply from North Africa to Central Europe as blend in existing pipelines – Potentials and costs. (1st March 2019) - Timmerberg, Sebastian; Kaltschmitt, Martin
Highlights: Renewable energy can be transported by mixing hydrogen into natural gas pipelines. Current pipelines limit hydrogen supply from North Africa to 9.5–23.2 TWh/a. North Africa can supply renewable hydrogen to Europe for min. 54–119 €/MWh in 2020. Abstract: Strong efforts are necessary to stem climate change. It requires to switch to renewable fuels. But as energy demand in Central Europe is high, renewable energy resources are of moderate quality, and available potentials are limited, energy imports from areas with beneficial renewable resources – such as North Africa – might be a promising option. Against this background this paper investigates the costs and potentials for hydrogen produced on the basis of electricity from wind and solar energy in North Africa and the subsequent transport as a blend with natural gas in existing pipelines. Linear optimization using hourly wind and solar data yields minimum hydrogen production cost. 2419 locations covering a 2° proximity of the existing natural gas pipeline infrastructure are considered in a lower and higher cost case for a near-term future (ca. 2020). Modell results provide lowest hydrogen production cost of 45 resp. 99 €/MWh. The production potential is in the range of PWh/a and therefore exceeds the hydrogen that can be transported in the existing infrastructure: Operating pipelines are potentially able to carry 10 vol% hydrogen in the natural gas feed with negligible adjustments to the infrastructure so that 9.5–23.2 TWh/a of hydrogen can be transported to Europe at minimum transport costs of 9 resp. 19 €/MWh. As these transport costs are low, supplying hydrogen leads to lower cost than transforming it to methane, Diesel or gasoline and is therefore the cheapest form of supplying a power based fuel. The hydrogen costs sum up to supply costs of 54 resp. 119 €/MWh free Central Europe.